Corporate culture and closure at Pepsi Cola - Alvesson, Mats, 1956- ([London] : SAGE, 2016)
This case study examines an account of the corporate culture at Pepsi Cola, as told by one of the company's former vice-presidents, John Sculley. Sculley's account could be seen as biased or self-promoting. However, it does provide unique insight into the corporate culture at Pepsi Cola in the late 1970s, in terms of values, norms, symbolism and understandings.
Originally Published in: Alvesson, M. (2012). Corporate Culture and Closure at Pepsi Cola. In Understanding organizational culture (2nd ed., pp. 173-176). London: SAGE Publications Ltd. ISBN: 9780857025586.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Pepsi-Cola Company; Corporate culture -- Case studies